Foreword - Atta-ur-Rahman (Current Analytical Chemistry, 2012)
Current Analytical Chemistry now enters in its 8th year of publication. It has become a leading journal in its field with a respectable impact factor. I would like to thank the Associate Editors, Guest Editors, Regional Editors as well as the Editorial Board Members for their constant efforts and guidance. I am also grateful to the authors for their valuable contributions.